ANALISIS KINERJA PEGAWAI DALAM PELAYANAN PUBLIK DI KANTOR CAMAT MANDAH KABUPATEN INDRAGIRI HILIR - jurnalmap map; Hajlianika ÔÇÄ; Kodrat Sunyoto; Arini Sulistyowati (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2021)
This research uses a descriptive method with a quantitative approach to a research variable. The variable in this study is the performance of employees in the District Office of Mandah, Indragiri Hilir Regency which consists of Employee Work Targets (SKP) and Work Behavior. The results of the study of the aspects of Employee Work Target included in the excellent category. The employee's work quantity always meets the set targets. The quality of employee work is occasionally an error. Work time completion of the task is always on time. Work suitability with the budget provisions, always in accordance with the budget provisions. From the aspect of Work Behavior, employees are included in the excellent category. The attitude of employees in providing services is always service oriented. Employee integrity always acts according to values, norms and ethics in the organization. The commitment of employees always prioritizes the interests of the service rather than the interests of themselves and / or groups. Employees always obey official regulations. Employees always work together with co-workers, superiors, subordinates. Employee leadership always has the ability to motivate and influence subordinates or others.